PARENT REPORTS OF THE PREVALENCE OF ADVERSE CHILDHOOD EXPERIENCES AMONG CHILDREN AND TEENS IN THE CAPE COAST METROPOLIS, GHANA - Afriyie, James; Bolton, Kelly; Nelson-Gardell, Debra (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Adverse childhood experiences (ACEs) — potentially traumatizing events that occur in childhood — have been linked to serious health problems later in life. Despite the documented negative effects of ACEs, and the high prevalence of ACEs in lower-middle-income countries, research about ACE prevalence is sparse for locales in Sub-Saharan Africa. This descriptive study examined the prevalence of ACEs among 800 children and teens in the Cape Coast Metropolis, Ghana, as reported by their parents (or caregivers), who were recruited from February to April 2021. Parent-reported sociodemographic characteristics and ACEs experienced by the children and teens were collected with the Center for Youth Wellness ACE Questionnaire (CYW ACE-Q). Analysis of the parents’ reports indicated that about 84.9% of the children and teens had been exposed to at least one ACE, 69.1% had experienced two or more ACEs, and 51.8% had experienced three or more ACEs. The most prevalent ACEs, according to the parents, were community violence (50.2%), separated parents (34.0%), physical abuse (33.4%), and emotional abuse (28.9%). This study thus reveals a high prevalence of ACEs in the Cape Coast Metropolis of Ghana, suggesting the need for policies and actions aimed at reducing community violence and protecting children from abuse in the Metropolis.